Phosphor-based green-emitting coatings for circadian lighting - Bispo-Jr, Airton G. [UNESP]; Lima, Sergio A.M. [UNESP]; Carlos, Luís D.; Ferreira, Rute A.S.; Pires, Ana M. [UNESP] (Elsevier, 2020)
Light-emitting diodes (LEDs) combining UV-emitting LEDs (UV-LED) with multi-coloured phosphors is one of the main strategies in solid-state lighting, opening new frontiers for the design of monochromatic sources. Greater relevance is found for green-emitting phosphors able to suppress the so-called “green-gap” limitation in electroluminescent LEDs. Moreover, applications in displays, traffic signals or phototherapy by human circadian rhythm regulation are envisaged. Here, we report the design of phosphor-based green-emitting coatings for circadian lighting combining UV-LEDs with the green-emitting Ba2SiO4:Eu(II) phosphor prepared by a new suitable and energetic-efficient approach and incorporated in plastic films (PMMA). This new route itself is advantageous as it yields phosphor with high emission quantum yield and avoid expensive energetic outlay through classic solid-state reactions. The phosphor green emission reveals an intriguing increase in the emission quantum yield (50 ± 5%) after the phosphor dispersion in PMMA. The emission of the LED prototypes operating at 3.2 V lies within the green spectral region with Commission International D''Éclairage coordinates of (0.182; 0.533), luminous efficacy of radiation (372 ± 1 lm·W−1) among the best values reported, and radiant photostability overseen for 180 h of operation.
Keywords: Ba2SiO4:Eu(II).; Circadian rhythm; Green-emitting phosphors; Solid-state lighting